Establishment of the fingerprint of ganoderma lucidum spore powder and study on the anti-inflammatory activity of ganoderma lucidum spore oil - Yu Zhang; Lihui Hou; Le Wang; Yunshan Si; Hongjuan Wen; Ying Gao; Xiuhua Yu (Guoji laonian yixue zazhi)
[Objective] Establishment of a fingerprinting assay for Ganoderma lucidum spore powder and investigation of the effects of Ganoderma lucidum spore oil on the inflammatory factors IL-1β, IL-6, and TNF-α. [Methods] High Performance Liquid Chromatography and High Performance Thin-layer Chromatography techniques were used to analyze the chemical composition of Ganoderma lucidum spore powder from different origins; MTT method was used to determine the cell viability; ELISA was used to determine the RAW264.7 IL-1β, IL-6 and TNF-α levels in cell supernatant. [Results] The HPLC fingerprints were calibrated with a total of 12 peaks, of which peaks 1-5 were ganoderic acid C2, ganoderic acid G, ganoderic acid B, ganoderic acid A, ganoderic acid D, respectively; the current version of the Pharmacopoeia method of HPTLC showed that 10 batches of samples complied with the regulations, and the quality of raw materials of different origins was found to be similar to that of the HPLC fingerprints after 2 unfoldings by using trichloromethane-acetonitrile-methanol-formic acid (26∶4 ∶1∶1) as the unfolding agent. The differences of the spots were significant and similar to the HPLC fingerprints. Ganoderma lucidum spore oil concentration less than or equal to 180 μg/mL had no significant effect on the activity of RAW264.7 cells; the protective effect on LPS-induced RAW264.7 cells was dose-dependent; compared with the model group, the medium-dose group (90 μg/mL) significantly decreased the expression of IL-1β (P<0.05), and the high-dose group (180 μg/mL) significantly decreased the expression of IL-6 and TNF-α release (P<0.05), slightly reduced IL-1β release, but not significant (P>0.05). [Conclusion] Ganoderma lucidum spore oil is used to reduce the inflammation of the body by inhibiting the release of inflammatory factors to achieve the protective effect on immune cells. The quality of spore powder can be initially identified by HPTLC, and HPLC fingerprinting can accurately control the quality of raw materials and guarantee the efficacy of Ganoderma lucidum spore oil.